Is Trade Liberalization One of the Determinants of Poverty in Upper Middle-Income Countries? - Tsaurai, Kunofiwa (Acta Universitatis Danubius. Œconomica, 2024)
This study examined whether trade openness is one of the determinants of poverty in upper middle-income countries using panel data (1991-2020) analysis methods such as fixed effects, pooled ordinary least squares (OLS) and fully modified ordinary least squares (FMOLS). Models 2 and 3 consistently produced results which show that trade openness reduced poverty in upper middle-income countries. The complementarity variables (1) trade openness and financial development and (2) trade openness and human capital development had a poverty reduction influence in upper middle-income countries. The study therefore urges the authorities in selected upper middle-income countries to craft and implement policies which further opens trade with other countries and which also enhances both human capital and financial development to alleviate poverty. A future study on the threshold levels of trade openness, human capital and financial development that significantly reduces poverty will add value to the existing literature.